2018
DOI: 10.1126/scitranslmed.aat6912
|View full text |Cite
|
Sign up to set email alerts
|

The DGCR5 long noncoding RNA may regulate expression of several schizophrenia-related genes

Abstract: A number of studies indicate that rare copy number variations (CNVs) contribute to the risk of schizophrenia (SCZ). Most of these studies have focused on protein-coding genes residing in the CNVs. Here, we investigated long non-coding RNAs (lncRNAs) within ten SCZ risk-associated CNV deletion regions (CNV-lncRNAs) and examined their potential contribution to SCZ risk. We used RNA-Seq transcriptomics data derived from postmortem brain tissue from control individuals without psychiatric disease as part of the Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Inhibition of a spliced lncRNA ARLNC1 localized in the nucleus and cytosol using either RNAi or ASO technologies has revealed its roles in androgen receptor signaling and growth of prostate cancer cells [109]. Knockdown of a spliced DGCR5 lncRNA that also localized in both cellular compartments using a mixture of siRNAs and ASOs has demonstrated involvement of this lncRNA in regulating a number of schizophrenia-related genes [110]. Overall, these techniques provided tremendous amount of support for functionality of various known types of lncRNAs.…”
Section: Rna Targetingmentioning
confidence: 99%
“…Inhibition of a spliced lncRNA ARLNC1 localized in the nucleus and cytosol using either RNAi or ASO technologies has revealed its roles in androgen receptor signaling and growth of prostate cancer cells [109]. Knockdown of a spliced DGCR5 lncRNA that also localized in both cellular compartments using a mixture of siRNAs and ASOs has demonstrated involvement of this lncRNA in regulating a number of schizophrenia-related genes [110]. Overall, these techniques provided tremendous amount of support for functionality of various known types of lncRNAs.…”
Section: Rna Targetingmentioning
confidence: 99%
“…Thus, we used a hypergeometric test to gauge the level of overlap between the intra-modular top neighbors of 16 3q29 interval genes and six curated lists of evidence-based IDD [59], ASD or SZ-risk genes [60][61][62][63][64], spanning a wide range of the allele frequency spectrum (Supp . Table S3.2).…”
Section: Nine 3q29 Interval Genes Form Transcriptomic Subnetwork Enrmentioning
confidence: 99%
“…Autism Research Initiative (SFARI); 3) 651 SZ-related genes identified byMeng et al (2018) [62] to demonstrate significant differential expression in the postmortem brain tissue of SZ cases/controls, identifiedfrom the PsychENCODE BrainGVEX dataset [63]; 4) 636 SZ-related genes shown by Fromer et al (2016) to demonstrate significant differential expression in the postmortem dorsolateral PFC tissue of SZ cases/controls, identified from the CommonMind Consortium dataset [60], 5) 340 SZ-risk genes adjacent to SZassociated genetic loci, identified by the most recent genome-wide association study (GWAS) [64] conducted by the Psychiatric Genomics Consortium (PGC); 6) 290 SZ-risk genes with exonic de novo mutations, identified via the Neuropsychiatric Disorder De Novo Mutations Database [61]. Four negative control gene-sets were curated from the following sources: 1) 25 AD-risk genes identified by the largest published GWAS meta-analysis conducted by the Genetic and Environmental Risk in AD/Defining Genetic, Polygenic and Environmental Risk for AD Consortium (GERAD/PERADES) [66]; 2) 67 PD-risk genes identified by the largest published GWAS meta-analysis conducted by the International PD Genomics Consortium [65]; 3) 98 IBD-related genes identified by the International IBD Genetics Consortium as "strong positional candidate genes" in GWAS-identified risk loci [67]; 4) 479 height-associated genes identified by the largest published GWAS meta-analysis conducted by the Genetic Investigation of Anthropometric Traits Consortium (GIANT)…”
mentioning
confidence: 99%
“…Based on the comprehensive literature review of GO term and KEGG pathway known to play key roles in SZ, the enriched terms and pathways were applied to reveal the mechanism underlying the cognitive dysfunction in patients with SZ. Moreover, the identified SZ signature was expected to contain a substantial percentage of SZ‐related genes . Here, a comprehensive literature review was thus performed to investigate the relevance of the signature to the etiology of SZ.…”
Section: Methodsmentioning
confidence: 99%